Effect of Fibrinogen on the Aggregation of Platelets by Adenosine Diphosphate - Cross, M. J (Thrombosis and Haemostasis, 1964)
The aggregation by adenosine diphosphate of washed human platelets suspended in plasma which had been heated at 100°C was considerably accelerated when normal plasma was also present. Fibrinogen enhanced this aggregation as effectively as normal plasma.